Autodesk Revit Architecture 2014 essentials - Duell, Ryan (Wiley, 2013)
Quickly learn essential Revit Architecture tools and techniques Autodesk Revit Architecture is the powerful, sophisticated building information modeling (BIM) software that has transformed the architectural design industry. This Autodesk Official Press guide is the perfect introduction to the powerful software for architects, designers, and students. Three Revit experts provide concise explanations, real-world examples, and plenty of hands-on exercises and tutorials. You'll soon master the basics and then find yourself using the software confidently, productively, and effectively.<